2021
DOI: 10.1108/rpj-10-2020-0240
|View full text |Cite
|
Sign up to set email alerts
|

Functional applications of 4D printing: a review

Abstract: Purpose Additive manufacturing has rapidly developed in terms of technology and its application in various types of industries. With this rapid development, there has been significant research in the area of materials. This has led to the invention of Smart Materials (SMs). The 4D printing is basically 3D printing of these SMs. This paper aims to focus on novel materials and their useful application in various industries using the technology of 4D printing. Design/methodology/approach Research studies in 4D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…Compared with SMAs, SMPs offer more deformation and less density. [558][559][560] SRP-based self-deployable structures are lightweight, selfexpanding, and have excellent carrying capacity, which makes them highly suitable for aerospace applications. [561] 3D printing of SRPs is showing remarkable potential in aerospace applications.…”
Section: Aerospace Sectormentioning
confidence: 99%
“…Compared with SMAs, SMPs offer more deformation and less density. [558][559][560] SRP-based self-deployable structures are lightweight, selfexpanding, and have excellent carrying capacity, which makes them highly suitable for aerospace applications. [561] 3D printing of SRPs is showing remarkable potential in aerospace applications.…”
Section: Aerospace Sectormentioning
confidence: 99%
“…Fused Deposition Modeling (FDM) as a subset of the Material extrusion (MEX) method is the simplest and cheapest 3D printing technology, the mechanism of which is the extrusion of molten filament on the bed and the underlying layers based on the digital design file [29][30][31]. The combination of MEX and CP (direct programming) by reducing and saving time and cost and adding the capability of complex and porous geometries can increase the medical applications of 4D printing [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…devices [7], textiles [8,9], metamaterials [10][11][12] and others. Detailed reviews on 4D printing can be found in [1,2,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%